Utilisation of alkaline hydrolysate of oil palm empty fruit bunch for biovanillin production - Zulkarnain, Aisyah (2017)
Interest in biovanillin production via biotechnological approach resulted from the expensive price of natural vanillin extracted from vanilla pod. Biovanillin is classified as natural flavour, thus offers a great potential to be commercialised to meet high demand of vanillin for worldwide user. Utilisation of lignocellulosic biomass as alternative substrate provides advantages on biovanillin production due to its abundancy and low cost. Therefore, this study aims to evaluate the potential of alkaline hydrolysate of OPEFB as an alternative substrate for biovanillin production via two-step bioconversion. However, 8 phenolic compounds were detected in the alkaline hydrolysate of OPEFB, namely; p-hydroxybenzoic acid, vanillic acid, vanillin, syringic acid, syringaldehyde, p-coumaric acid, p-hydroxybenzaldehyde and ferulic acid, with the highest concentration was p-hydroxybenzoic acid. Thus, a model of formulated phenolic compounds was used to study the effect of those phenolic compounds towards vanillic acid production which known as primary intermediate compound in two-step bioconversion as a response in the two-level factorial design. Prior for two-step bioconversion process, the potential fungi were screened on their abilities to produce vanillic acid and biovanillin. Aspergillus niger ATCC6257 and Aspergillus niger EFB1 were used for vanillic acid production while the Phanerochaete chrysosporium UIA and Phanerochaete chrysosporium EFB1 were used for biovanillin production. For vanillic acid production using glucose (before the addition of ferulic acid), A. niger ATCC6257 produced 51.3% molar yield of vanillic acid, indicates 0.18 fold increase of vanillic acid than A. niger EFB1 (43.6%). Whereas, P. chrysosporium UIA showed 30.6% molar yield of biovanillin, indicates 0.37 fold increase than P. chrysosporium EFB1 which recorded 22.4% molar yield of biovanillin. Hence, A. niger ATCC6257 and P. chrysosporium UIA were selected to be used for two-step bioconversion of alkaline hydrolysate of OPEFB to biovanillin. The results showed 41% and 39% molar yield of vanillic acid and biovanillin, respectively, were able to be produced from two-step bioconversion of alkaline hydrolysate of OPEFB. On the other hand, only ferulic acid, p-hydroxybenzoic acid and p-coumaric acid are significant factors (p<0.05) in two-level factorial model. Ferulic acid plays a great factor in producing vanillic acid, whereas the interaction with p-hydroxybenzoic, and p-coumaric acid show negative effect that inhibit vanillic acid production. In overall, alkaline hydrolysate of OEPFB exhibited as potential alternative substrate for biovanillin production via two-step bioconversion.